Perivascular fat tissue and vascular aging: A sword and a shield - Yan Wang; Xianmin Wang; Yang Chen; Yuelin Zhang; Xianjie Zhen; Siyu Tao; Jinfang Dou; Peng Li; Guangjian Jiang (Elsevier, 2024)
The understanding of the function of perivascular adipose tissue (PVAT) in vascular aging has significantly changed due to the increasing amount of information regarding its biology. Adipose tissue surrounding blood vessels is increasingly recognized as a key regulator of vascular disorders. It has significant endocrine and paracrine effects on the vasculature and is mediated by the production of a variety of bioactive chemicals. It also participates in a number of pathological regulatory processes, including oxidative stress, immunological inflammation, lipid metabolism, vasoconstriction, and dilation. Mechanisms of homeostasis and interactions between cells at the local level tightly regulate the function and secretory repertoire of PVAT, which can become dysregulated during vascular aging. The PVAT secretion group changes from being reducing inflammation and lowering cholesterol to increasing inflammation and increasing cholesterol in response to systemic or local inflammation and insulin resistance. In addition, the interaction between the PVAT and the vasculature is reciprocal, and the biological processes of PVAT are directly influenced by the pertinent indicators of vascular aging. The architectural and biological traits of PVAT, the molecular mechanism of crosstalk between PVAT and vascular aging, and the clinical correlation of vascular age-related disorders are all summarized in this review. In addition, this paper aims to elucidate and evaluate the potential benefits of therapeutically targeting PVAT in the context of mitigating vascular aging. Furthermore, it will discuss the latest advancements in technology used for targeting PVAT.